Innovative Aspects of Development of the Waste Recycling Industry in the New Economic Context: Problems and Prospects - MOROZYUK, Yuriy Vitaliyovych; SHARKOVA, Antonina Vasilievna; MERKULINA, Irina Anatolievna; VASILYEVA, Oksana Nikolaevna (Journal of Environmental Management and Tourism, 2017)
The article considers the investment potential in the waste recycling industry in the Moscow region of Russia. According to official data, about 63 mln tons is produced annually in Russia; about 10% is recycled. Due to the increasing volume of production and services provided, waste disposal has become a must for any large city – otherwise, a metropolis can sink in its own waste that does not find room on the periphery. Establishment of a safe and efficient system for handling waste of production and consumption is more important today than ever before. The engineering infrastructure has exhausted its capacity and cannot cope with the increased volume. According to the Federal Supervisory Natural Resources Management Service, there are less than 400 enterprises for sorting and disposing of household waste operating in the country; there are a total of 1,092 landfills. None of the regions switched to the industrial waste recycling. The market of secondary resources is poorly developed: only 4-5% of the total volume of generated household waste is involved in recycling.